PENGEMBANGAN KINERJA DAN KARIR AKADEMIK - Dirga Lestari AS (Faculty of Economics and Business Mulawarman University, 2015)
To realize the ideals of higher education in Indonesia became international university takes the hard work of all elements of universities to improve and develop the quality of learning. One program that should receive priority development is professional development of lecturers as the principal element of the college. Faculty professional development is very important to improve the quality of higher education in Indonesia. Efforts to develop and improve the performance and career development of faculty is primarily a university requirement that never ends. Professional development programs need to be implemented on a regular lecturer and continuous in order to truly create the lecturers who are able to carry out their duties in a professional manner, that is produce scientists and experts in various fields, the intellectual life of the nation in the broadest sense and to develop human persons were able to bring complete Indonesian Indonesian become a developed nation and dignity. Keywords : Performance, Academic Career